THE EFFECT OF LEARNING HOURS OF COMPETENCY DEVELOPMENT AND EMPLOYEE PERFORMANCE ON ORGANIZATIONAL PERFORMANCE AT A GOVERNMENT INSTITUTION IN INDONESIA - Ari Sudewo, Perdhana; Aruan Sulastri, Bintang (Jurnal Administrasi Negara, 2022)
The merit system has been mandated by the State Civil Apparatus (ASN) Law, requiring competency development of a minimum of 20 Learning Hours for every Civil Servant (PNS) each year and implementation of employee performance management integrated with organizational performance management. From a study conducted by the State Civil Apparatus Commission (KASN) and research on ASN management, it is concluded that the merit system in Indonesian ASN management has not been implemented effectively. Considering that the implementation of the merit system must continue to be supported through continuous improvement, this research aims to conduct an evaluative study through a study Learning Hour's achievement of employee competency development and employee performance and its influence on performance of government organizations. The research was conducted using data from 2020 at one of the Government Institutions that became the object of research using data on Learning Hour's achievement of employee competency development, data on employee performance appraisal results, and Government Agency Performance Accountability evaluation data (AKIP) as an organizational performance data. The study used all data on 43 independent organization units the research population at a Government Institution. Data analysis was carried out quantitatively through multiple linear regression analysis. The analysis results show that the variable of Learning Hour's achievement of employee competency development and employee performance together does not have a significant correlation to organizational performance variables in Government Institutions, and employee performance variables have more influence on organizational performance than Learning Hour's achievement employee competency development. Results of this research are expected to be used as evaluation sources and input in improving the quality of the implementation of the merit system of Indonesian ASN management, especially in Government Institutions that are the object of research